Aluminum member and manufacturing method thereof
Friction stir processing at low speed and tilt creates a fine grain region in aluminum, addressing the insufficient strength of high-purity aluminum, enhancing both mechanical properties and conductivity for cryogenic applications.
Patent Information
- Application Number
- JP2020129167
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-07-30
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2040-07-30
AI Technical Summary
Existing methods fail to sufficiently refine the crystal grain size of aluminum with a purity of 5N or more, resulting in insufficient strength, which limits its use in applications requiring both high purity and strength.
A method involving friction stir processing with a rotating cylindrical jig at a low speed and specific tilt angle to create a fine grain region with a grain size of less than 20 μm, combined with a fine grain region exposed on the surface, to enhance strength and conductivity.
The method achieves an aluminum member with a purity of 5N or more and sufficient strength, suitable for cryogenic applications by refining the grain size to improve mechanical properties and conductivity.
Smart Images

Figure 0007610214000005 
Figure 0007610214000006 
Figure 0007610214000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an aluminum component and a method for manufacturing the same. [Background technology]
[0002] Aluminum (Al) with a purity of 99.999% by mass (5N) or more has extremely high electrical and thermal conductivity at cryogenic temperatures, and is therefore often used as an electrical and thermal conductor in cryogenic devices. However, the higher the purity of Al, the lower its strength tends to be, limiting its applications. For applications requiring strength, methods such as bonding high-strength materials to Al of 5N or higher or adding different elements (alloying) are used, but these methods have problems such as being expensive and compromising the excellent properties of Al of 5N or higher.
[0003] One method for improving the strength of metal materials such as Al is to refine the crystal grain size. Non-Patent Document 1 discloses that high-pressure massive plastic processing can be used to refine the crystal grain size of Al with a purity of 99.99 mass% (4N) to about 2 μm, thereby increasing the strength to a hardness of 40 HV. Non-Patent Document 2 discloses that friction stir processing (FSP) can be performed on 4N Al at a moving speed of 200 mm / min and a rotation speed of 300 to 1500 rpm to reduce the crystal grain size to a minimum of 2 μm or less. [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] Yoshiharu Hotta, "Ultrafine Structure Control by Severe Plastic Deformation", Light Metals, Japan Institute of Light Metals, 2010, Vol. 60, No. 3, pp. 134-141 [Non-Patent Document 2] Hiroki Mori, "Structure Optimization of Ultrafine-Grained Aluminum Materials Using Friction Stir Processing," Doctoral Dissertation, Graduate School of Osaka Prefecture University, 2011 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the conventional techniques disclosed in Non-Patent Documents 1 and 2 have not been able to sufficiently refine the grain size of 5N or more Al. Non-Patent Document 1 discloses that when the purity of Al is high, cross slip and / or recovery of dislocations easily proceeds, and sufficient accumulation of dislocations does not occur, resulting in no refinement of the grain size. Non-Patent Document 2 discloses that even if the conditions that achieved a minimum grain size of 2 μm or less in 4N Al are applied to 5N Al, the grain size will be about 30 μm, and that trace amounts of impurity elements of only about 100 ppm have a significant effect on this large difference in grain size. From the above, it cannot be said that the prior art discloses a method for sufficiently refining the grain size of Al having a grain size of 5N or more. Therefore, in the prior art, Al having a grain size of 5N or more has insufficient strength overall, and it is difficult to use it for applications requiring strength.
[0006] The present invention has been made in consideration of these circumstances, and one of its objects is to provide an aluminum component having a purity of 5N or more and having sufficient strength in at least a portion thereof, and a method for manufacturing the same. [Means for solving the problem]
[0007] Aspect 1 of the present invention is A fine grain region having a grain size of less than 20 μm; The aluminum component has a purity of 99.999% by mass or more.
[0008] Aspect 2 of the present invention is An intermediate grain region having a grain size of 20 μm or more and less than 150 μm; The aluminum member according to aspect 1, further comprising a coarse crystal grain region having a crystal grain size of 150 μm or more.
[0009] Aspect 3 of the present invention is 3. The aluminum member according to claim 1 or 2, wherein the fine crystal grain region has an average crystal grain size of 5 μm or less.
[0010] A fourth aspect of the present invention is At least one surface of the fine grain region is less than 0.01 mm 2 The aluminum member according to any one of aspects 1 to 3, wherein the metal oxide layer is continuously present over the above area.
[0011] A fifth aspect of the present invention is The present invention relates to an electric and thermal conductive material for cryogenic use, comprising the aluminum member according to any one of the first to fourth aspects.
[0012] A sixth aspect of the present invention is The method for producing the aluminum member according to any one of aspects 1 to 4 includes a friction stirring step of moving a rotating cylindrical jig while pressing it against the surface of an aluminum plate having a purity of 99.999% by mass or more, and the moving speed of the cylindrical jig is 100 mm / min or less.
[0013] A seventh aspect of the present invention is The method according to claim 6, wherein in the friction stirring step, the cylindrical jig is moved with its rotation axis tilted by 3° or more from a perpendicular to the surface of the aluminum plate in a direction opposite to the moving direction of the cylindrical jig. Effect of the Invention
[0014] According to the embodiments of the present invention, it is possible to provide an aluminum member having a purity of 5N or more and having sufficient strength at least in a part thereof, and a manufacturing method thereof. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is an inverse pole figure (IPF) map of Example 1 obtained by the EBSD method. [Diagram 2] FIG. 2 is an enlarged view of the fine grain region 1 of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present inventors have conducted research from various angles in order to realize an aluminum member having a purity of 5N or more and having sufficient strength in at least a part thereof.
[0017] The present inventors focused on friction stir processing (FSP) as a method for realizing the above-mentioned aluminum member. In FSP, a rotating cylindrical jig is pressed against the workpiece and moved, thereby applying strong strain to the workpiece. In research on FSP, it is believed that this strong strain can cause dynamic recrystallization in the workpiece, forming fine recrystallized grains. According to the prior art, particularly Non-Patent Document 2, it is speculated that in FSP, by moving the cylindrical jig at a relatively high speed (specifically, 200 mm / min), the processing heat can be reduced and grain growth can be suppressed. As a result of extensive research, the inventors have found that, contrary to conventional technical ideas, by moving a cylindrical jig at a relatively slow speed (100 mm / min or less), it is possible to realize a fine crystal grain region with a crystal grain size of less than 20 μm in Al with a purity of 5N or more, which was not achievable with conventional technology, and further that the portion including the fine crystal grain region has sufficient strength (Vickers hardness).
[0018] The details of each requirement stipulated in the embodiment of the present invention are shown below. Note that the "purity" of the aluminum member (and the aluminum plate) according to the embodiment of the present invention refers to the value obtained by subtracting the total content (mass%) of the three main impurities (Si, Fe, and Cu) from 100 mass%.
[0019] The aluminum member according to the embodiment of the present invention has a purity of 99.999% by mass or more. This makes it possible to improve the cryogenic conductivity characteristics of the aluminum member. Preferably, the purity is 99.9995% by mass or more.
[0020] The aluminum member according to the embodiment of the present invention may contain 10 other trace impurity elements (Ti, Mn, Mg, B, Cr, Ga, Ni, V, Zn, Zr) in addition to the three main impurity components (Si, Fe, and Cu). The content of the other 10 trace impurity elements is preferably 0.001 mass% or less. This can improve the cryogenic conductivity properties of the aluminum member.
[0021] The aluminum member according to the embodiment of the present invention includes a fine crystal grain region having a crystal grain size of less than 20 μm, which allows an aluminum member to have sufficient strength at least in a portion (i.e., a portion including the fine crystal grain region).
[0022] The fine crystal grain region has an average crystal grain size of less than 20 μm, preferably 5 μm or less, more preferably 3 μm or less, as measured in a 100 μm square. This can further improve the strength of the fine crystal grain region. The lower limit of the average crystal grain size in the fine crystal grain region is not particularly limited, but can be, for example, 0.1 μm or more.
[0023] The fine grain region is 0.01 mm 2 It is preferable that the above-mentioned continuous portions are provided, which can improve the strength.
[0024] The fine crystal grain region preferably has a portion exposed on at least one surface of the aluminum member, thereby improving strength against external forces. In addition, the fine crystal grain region is 0.01 mm or less in size on at least one surface of the aluminum member. 2 It is preferable that the surface area of the stratum is continuous over an area of 1 mm or more, and more preferably 1 mm 2 More preferably, 10 mm 2 More preferably, 40 mm or more 2 This improves the strength against external forces. There is no particular upper limit to the above area, but it is preferably 1.5 m2 It may be less than 0.001% by area on at least one surface of the aluminum member, more preferably 0.1% by area or more, even more preferably 1% by area or more, and even more preferably 4% by area or more. The upper limit of the area ratio is not particularly limited, but it may be 100% by area or less. The area of the continuous fine crystal grain region on the surface of the aluminum member may be measured, for example, by performing EBSD analysis on the surface, which will be described later. Alternatively, EBSD analysis may be performed on a cross section of the surface that is parallel to the longitudinal direction (or transverse direction) of the aluminum member and perpendicular to the surface, and this may be repeated at regular intervals (for example, 0.02 mm) in the transverse direction (or longitudinal direction) to measure the area of the continuous fine crystal grain region on the surface of the aluminum member.
[0025] The fine crystal grain region preferably has a portion having a thickness of 0.10 mm or more measured from at least one front surface to the back surface of the aluminum member. More preferably, the portion has a thickness of 0.20 mm or more, and even more preferably, the portion has a thickness of 0.30 mm or more. This can improve the strength against external forces from the outside. Also, it is preferable that the fine crystal grain region has a portion having a ratio of the thickness of the fine crystal grain region to the length from the front surface to the back surface of the aluminum member of 10% or more, more preferably, 20% or more, and even more preferably, 30% or more. This can improve the strength against external forces from the outside.
[0026] The area of the fine crystal grain region may decrease from at least one front surface to the back surface of the aluminum member according to the embodiment of the present invention. Also, the area of the fine crystal grain region may differ between at least one front surface and the back surface.
[0027] The aluminum member according to the embodiment of the present invention may include a non-fine crystal grain region having a crystal grain size of 20 μm or more in addition to the fine crystal grain region. For example, the aluminum member may further include an intermediate crystal grain region having a crystal grain size of 20 μm or more and less than 150 μm, and a coarse crystal grain region having a crystal grain size of 150 μm or more. From the viewpoint of improving strength, it is preferable to make the fine crystal grain region larger, it is preferable to make the intermediate crystal grain region and the coarse crystal grain region smaller, and it is more preferable to make the coarse crystal grain region smaller. In one embodiment, which is preferable from the viewpoint of improving strength, the aluminum member is composed of the fine crystal grain region and the intermediate crystal grain region, and in the most preferable embodiment, which is preferable from the viewpoint of improving strength, the aluminum member is composed of the fine crystal grain region. On the other hand, by including a coarse crystal grain region (and / or an intermediate crystal grain region), the number of crystal grain boundaries is reduced, and thus the cryogenic conductivity characteristics can be improved. In a preferred embodiment from the viewpoint of achieving a good balance between strength and cryogenic conductivity characteristics, the aluminum member includes a fine crystal grain region in a portion where strength is required, and includes a coarse crystal grain region (and / or an intermediate crystal grain region) in the other portion.
[0028] In an embodiment of the present invention, the grain size refers to the diameter of a region surrounded by a grain boundary, which is a grain boundary with a crystal orientation difference of 5° or more as a result of electron backscatter diffraction (EBSD) analysis, i.e., the equivalent circle diameter, and the average grain size refers to the average grain size in a specified area (e.g., 100 μm□) of the surface analyzed by EBSD. As for the coarse grain region, a simple method of determining the average grain size is to draw a straight line on the surface analyzed by EBSD, and divide the length of the line by the number of grain boundaries that intersect with the line to obtain the average grain size of the coarse grain region.
[0029] The aluminum member according to the embodiment of the present invention may have any shape, for example, a plate shape, a thin wire shape, or a cylinder shape.
[0030] The cryogenic electrical and thermal transfer material according to the embodiment of the present invention includes the aluminum member described above, and may include other members in addition to the aluminum member as long as the object of the present invention is achieved.
[0031] A manufacturing method of an aluminum component according to an embodiment of the present invention includes a friction stirring step of moving a rotating cylindrical jig on the surface of an aluminum plate having a purity of 99.999% by mass or more while pressing the cylindrical jig against the surface, and the moving speed of the cylindrical jig is 100 mm / min or less. This makes it possible to form a fine crystal grain region having a crystal grain size of less than 20 μm in a location where a strong strain of 5 N or more is applied by the cylindrical jig.
[0032] In the above-mentioned friction stirring process, the aluminum plate to be treated may be one piece. The friction stirring process may be performed multiple times on the same location on the surface of one aluminum plate, or may be performed once or multiple times on different locations. By performing the friction stirring process on the entire surface (and / or back surface) of one aluminum plate, a fine crystal grain region can be formed over the entire area of the aluminum plate.
[0033] In the above friction stir process, the aluminum plate to be treated may be a plurality of plates, for example, two plates. In this case, the two aluminum plates are placed on the same plane, one end surface of the two aluminum plates is brought into contact with each other, and a rotating cylindrical jig is pressed against the contact portion of the surface of the two aluminum plates while being moved. As a result, the two aluminum plates are joined, and an aluminum member in which a fine crystal grain region with a crystal grain size of less than 20 μm is formed at a place where a strong strain is applied near the joint can be obtained. The friction stir process may be performed multiple times on the joint, or may be performed on other parts than the joint. It is preferable that the thicknesses of the aluminum plates are the same, because the cylindrical jig can be pressed uniformly against them. In addition, it is preferable that the aluminum plates have at least one flat end surface so that they can be contacted with each other without any gaps.
[0034] In the friction stirring step, the moving speed of the cylindrical jig is preferably 80 mm / min or less, more preferably 20 mm / min or less, and even more preferably 8 mm / min or less, which can reduce the average crystal grain size of the fine crystal grain region.
[0035] In the above friction stirring process, it is preferable to move the cylindrical jig with the rotation axis of the cylindrical jig tilted by 3° or more from the perpendicular line of the aluminum plate surface in the opposite direction to the moving direction of the cylindrical jig. This makes it easier for the rotation force generated by the cylindrical jig to be directed from the surface of the aluminum plate to the inside, making it easier to expand the fine crystal grain region. The upper limit of the angle at which the cylindrical jig is tilted is, for example, 85°.
[0036] In the above friction stirring process, the rotation speed of the cylindrical jig is preferably more than 1500 rpm, more preferably 2000 rpm or more, and even more preferably 3000 rpm or more. This makes it easier to refine the crystal grains. The upper limit of the rotation speed of the cylindrical jig is not particularly limited, but is, for example, 20000 rpm or less.
[0037] In the above friction stir process, the indentation depth of the cylindrical jig into the aluminum plate surface is preferably 0.3 mm or more and 3 mm or less, more preferably 0.3 mm or more and 0.5 mm or less. The ratio of the indentation depth to the thickness of the aluminum plate is preferably 6% or more and less than 100%, more preferably 37.5% or more and 62.5% or less. This allows the friction stir process to be performed at an appropriate processing speed, making it easier to obtain a fine crystal grain region. After the friction stir process, a recess may be formed on the surface of the aluminum member depending on the indentation depth of the cylindrical jig.
[0038] In the above friction stir process, the material of the cylindrical jig may be a material having a higher hardness than aluminum, for example, tool steel, etc. The tip shape of the cylindrical jig may be, for example, spherical, or may have another shape.
[0039] In the above friction stirring process, the aluminum plate with a purity of 99.999% by mass or more that serves as the material to be treated can be prepared by a known method, for example, by preparing an aluminum piece with a purity of 99.999% by mass or more by a known method such as a segregation method, a three-layer electrolysis method, a zone melting refining method, an ultra-high vacuum melting refining method, or a combination thereof, and then rolling the aluminum piece.
[0040] In the above-mentioned friction stirring process, the thickness of the aluminum plate to be treated is preferably 0.5 mm or more, more preferably 0.7 mm or more. This can suppress the deformation of the aluminum plate in the friction stirring process. The upper limit of the thickness of the aluminum plate is not particularly limited, but is, for example, 5 mm or less. In addition, the in-plane shape of the aluminum plate is not particularly limited, but can be, for example, a square or a rectangle.
[0041] In the aluminum component obtained after the friction stir process, the area of the fine crystal grain region may decrease from the front surface against which the cylindrical tool is pressed toward the back surface. This is believed to be because the area to which strong strain is applied by the cylindrical tool decreases from the front surface against which the cylindrical tool is pressed toward the back surface.
[0042] In the aluminum member obtained after the friction stir process, a strong strain can be applied continuously from the surface against which the cylindrical jig is pressed to the back surface, so that the fine crystal grain region can be continuous from the surface to the back surface, and in some cases, the fine crystal grain region can be continuous from the surface to the back surface. In many cases, the area of the fine crystal grain region differs between the surface against which the cylindrical jig is pressed and the back surface, and the area of the fine crystal grain region can be larger on the surface against which the cylindrical jig is pressed than on the back surface. This is thought to be because a strong strain is applied over a wider area on the surface against which the cylindrical jig is pressed.
[0043] In the areas where almost no strain is applied in the friction stir process, grain refinement does not occur, and the areas may become coarse grain regions with grain sizes of, for example, 150 μm or more.
[0044] In the aluminum member obtained after the friction stir process, the area of the coarse crystal grain region may be smaller on the surface against which the cylindrical jig is pressed than on the back surface. That is, in the aluminum member obtained after the friction stir process, the area of the coarse crystal grain region may differ between at least one surface and the back surface. This is thought to be because the surface against which the cylindrical jig is pressed is subjected to a larger range of strong strain, and conversely, the area to which almost no strain is applied is narrower.
[0045] The friction stir process may also form an intermediate crystal grain region having a crystal grain size of 20 μm or more and less than 150 μm. The intermediate crystal grain region may be formed, for example, between a fine crystal grain region and a coarse crystal grain region. This is because the influence of the cylindrical jig is smaller between the fine crystal grain region and the coarse crystal grain region than between the fine crystal grain region and the coarse crystal grain region, and is larger than between the fine crystal grain region and the coarse crystal grain region.
[0046] Within the scope of achieving the object of the present invention, the manufacturing method of the aluminum component according to the embodiment of the present invention may include other steps, for example, a step of processing into various shapes such as thin wires, a step of flattening the surface of the aluminum component, and / or a step of removing coarse crystal grain regions, etc. EXAMPLES
[0047] The following examples are provided to more specifically describe the embodiments of the present invention. The embodiments of the present invention are not limited to the following examples, and may be modified as appropriate within the scope of the above and below-described aims, and all of these are included in the technical scope of the embodiments of the present invention.
[0048] An aluminum piece (thickness 20 mm) with a purity of 5N prepared by a known method was cold-rolled at room temperature to obtain an aluminum plate with a width of 10 mm, a length of 100 mm, and a thickness of 0.8 mm. The rolling direction was the length direction. Two of these aluminum plates were prepared and placed on the same plane, and the end faces (width 10 mm x thickness 0.8 mm) in the length direction of the two plates were brought into contact with each other, and a rotating cylindrical jig was pressed against the contact portion of the surfaces of the two plates while moving at a speed of 5 mm / min and a distance of 10 mm. At this time, the cylindrical jig used was made of tool steel SKD61, the tip shape was a sphere with a diameter of 5 mm and a curvature of 5.4 mm, the rotation speed of the cylindrical jig was 3000 rpm, and the rotation axis of the cylindrical jig was moved at an inclination of 3° or more from the perpendicular line of the aluminum plate surface in the opposite direction to the movement direction of the cylindrical jig. The pressing depth of the cylindrical jig into the aluminum plate surface was 0.35 mm. In this manner, an aluminum member of Example 1 was obtained. Furthermore, the moving speed of the cylindrical jig and the indentation depth into the aluminum plate surface were changed as shown in Table 1, and aluminum members of Examples 2 and 3 were obtained.
[0049] [Table 1]
[0050] Aluminum pieces (thickness 20 mm) with a purity of 4N, 5N, or 6N, prepared by a known method, were cold-rolled at room temperature to obtain aluminum members (aluminum plates) of Comparative Examples 1 to 5. (Only Comparative Example 4 had a plate thickness of 1.0 mm, and the others had a plate thickness of 0.8 mm.) Then, Comparative Examples 4 and 5 were subjected to a heat treatment at 500°C for 3 hours in a nitrogen atmosphere.
[0051] Examples 1 to 3 and Comparative Examples 1 to 5 were evaluated as follows.
[0052] <Impurity concentration measurement> The method for measuring the impurity concentration includes glow discharge mass spectrometry (GD-MS) or solid-state optical emission spectrometry. For Examples 1 to 3 and Comparative Examples 4 and 5, the impurity concentration was measured by GD-MS, and for Comparative Examples 1 to 3, the impurity concentration was measured by solid-state optical emission spectrometry. The contents (mass%) of the main elements Fe, Si, and Cu, as well as their total content, and the total content of 10 other trace impurity elements (Ti, Mn, Mg, B, Cr, Ga, Ni, V, Zn, Zr) are shown in Table 2.
[0053] [Table 2]
[0054] <Average grain size measurement> In Examples 1 to 3, the cross sections parallel to the length direction (rolling direction) and thickness direction were mirror-finished by buff polishing using colloidal silica. Then, the cross sections were subjected to crystal orientation analysis by electron backscatter diffraction (EBSD) method. The step size in the EBSD measurement was set to 0.2 μm, and the boundary where the orientation difference between adjacent pixels was 5° or more was determined to be the crystal grain boundary.
[0055] As an example, Figure 1 shows an IPF map obtained by the EBSD method in a cross section parallel to the length direction (rolling direction) and thickness direction of Example 1. For Figure 1 (and Figure 2 described later), an original drawing in which the differences in crystal planes can be identified by color has been submitted as a document to be submitted at the same time as this application so that the differences in crystal planes can be understood in more detail. Please refer to this original drawing as necessary. In FIG. 1, a fine crystal grain region 1 was observed in the region (approximately 4 mm in the length direction) on the surface of the aluminum member where the cylindrical jig was pressed. Note that the fine crystal grain region 1 has very fine crystal grains and a large number of crystal grain boundaries (black lines), so it appears almost black in the IPF map of FIG. 1, which is not enlarged. In addition, a coarse crystal grain region 3 was observed in the region on the surface of the aluminum member where the cylindrical jig was not pressed and in the region away from the fine crystal grain region 1, and an intermediate crystal grain region 2 was observed between the fine crystal grain region 1 and the coarse crystal grain region 3. Note that in Example 1, a fine crystal grain region was formed over the entire region (approximately 4 mm × 10 mm) on the surface of the aluminum member where the cylindrical jig was pressed. Examples 2 and 3 also had a similar structure.
[0056] FIG. 2 shows an enlarged view (100 μm×100 μm) of the fine crystal grain region 1 in FIG. 1. The average crystal grain size in FIG. 2 was calculated, and it was taken as the average crystal grain size of the fine crystal grain region of Example 1. For the intermediate crystal grain region, all of the intermediate crystal grain regions 2 included in FIG. 1 were extracted, and the average crystal grain size in the extracted intermediate crystal grain region was calculated. For the coarse crystal grain region, a straight line of about 15 mm in length was drawn in the cross section parallel to the length direction (rolling direction) and thickness direction, and the number of crystal grain boundaries intersecting with the straight line was counted. The length of the straight line was divided by the number of crystal grain boundaries to obtain the crystal grain size. The crystal grain boundaries were counted at any two or more points on the cross section, and the average value of the obtained crystal grain sizes was taken as the average crystal grain size of the coarse crystal grain region. For Examples 2 and 3, the average crystal grain size was measured in the same manner as in FIG.
[0057] In Comparative Examples 1 to 5, the cross section parallel to the rolling direction and the sheet thickness direction was mirror-finished, and the microstructure was revealed by etching. Then, a straight line of about 15 mm in length was drawn in the rolling direction, and the number of grain boundaries intersecting with the line was counted. The length of the line was divided by the number of grain boundaries to obtain the grain size. The grain boundaries were counted at any two or more points on the observation surface, and the average value of the obtained grain sizes was used as the average grain size.
[0058] <Hardness measurement> As an index of whether at least a portion of the obtained aluminum member has sufficient strength, the Vickers hardness (HV) was measured using a micro Vickers hardness tester. Vickers hardness is a value measured according to JIS Z2244:2009 "Vickers hardness test - Test method". To measure Vickers hardness, a square pyramid diamond indenter is pressed into the surface of an aluminum member, and after the test force is released, the diagonal length of the indentation remaining on the surface is calculated. The test load may be adjusted as desired. For example, as described in JIS Z2244:2009, the thickness of the test piece and the test load may be selected so that the thickness of the test piece is 1.5 times or more the diagonal length of the indentation. A suitable example of the test load is 0.05 kgf when the thickness of the aluminum member is 300 μm or more, and 0.005 to 0.01 kgf when the thickness is less than that. The test load may be adjusted so that the indentation size is appropriate depending on the hardness of the test piece.
[0059] In Examples 1 to 3, the hardness was measured at four or more arbitrary locations in the area (approximately 4 mm × 10 mm) where the cylindrical jig was pressed on the surface of the aluminum member, and in Comparative Examples 1 to 3, the hardness was measured at four or more arbitrary locations without any particular designation of measurement locations, and the average value of each measurement location was calculated. In Comparative Examples 4 and 5, the hardness was not measured. A hardness of 35 (HV) or more was determined to be sufficient strength.
[0060] The measurement results of the average crystal grain size and hardness of Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 3. In Examples 1 to 3, the average crystal grain size of the fine crystal grain region is shown in the "average crystal grain size" column. Although not shown in Table 3, the average crystal grain size of the coarse crystal grain region in Examples 1 to 3 was 890 μm, and the average crystal grain size of the medium crystal grain region in Example 1 was 110 μm. Furthermore, in Comparative Examples 1 to 5, there were no fine crystal grain regions with crystal grain sizes less than 20 μm.
[0061] [Table 3]
[0062] From the results in Table 3, the following can be considered. All of Examples 1 to 3 in Table 3 are examples that satisfy all the requirements stipulated in the embodiment of the present invention, and had sufficient strength despite the purity of 5N or more. In particular, Examples 1 and 2, unlike Example 3, had a cylindrical jig moving speed of 80 mm / min or less, which satisfied the preferred range, and therefore the average crystal grain size in the fine crystal grain region was 5 μm or less, and the hardness was 40 (HV) or more, showing better results. Furthermore, in Example 1, unlike Examples 2 and 3, the cylindrical jig moving speed was 20 mm / min or less, which satisfied the more preferred range, and therefore the average crystal grain size in the fine crystal grain region was 3 μm or less, and the hardness was 60 (HV) or more, showing even better results. On the other hand, when the purity was reduced to 4N as in Comparative Example 1, sufficient strength was exhibited, but in Comparative Examples 2 and 3, in which the purity was 5N or more, the strength was insufficient because the fine crystal grain region with a crystal grain size of less than 20 μm was not included.
[0063] <Evaluation of cryogenic conductivity characteristics (evaluation of residual resistance ratio)> Electrical resistance was measured by the four-terminal method. The electrical resistance was measured when the sample was immersed in liquid helium and when immersed in water controlled at 23°C, and the ratio of the electrical resistance when immersed in liquid helium to the electrical resistance measured at 23°C (residual resistance ratio: RRR) was obtained. A residual resistance ratio of 1000 or more was determined to indicate excellent cryogenic conductivity characteristics. In Example 1, the electrical resistance was measured so that the area (approximately 4 mm x 10 mm) where the cylindrical jig was pressed against the surface of the aluminum member was included between the terminals.
[0064] The measurement results of the residual resistance ratio are shown in Table 4. In Example 1, the average crystal grain size of the fine crystal grain region is shown in the "average crystal grain size" column.
[0065] [Table 4]
[0066] The results in Table 4 can be considered as follows: Example 1 is an example that satisfies all of the requirements stipulated in the embodiments of the present invention, and since the purity was 5N or more, the cryogenic conductivity characteristics were excellent. On the other hand, in Comparative Example 4, since the purity was 4N, the cryogenic conductivity characteristics were insufficient. It should be noted that both Example 1 and Comparative Example 5 have a purity of 5N or more, but Example 1 has a large number of crystal grain boundaries, which results in a high resistance value at cryogenic temperatures, and is therefore considered to have a slightly lower residual resistance ratio than Comparative Example 5. Although the residual resistance ratios of Examples 2 and 3 were not measured, they are considered to have a larger average crystal grain size in the fine crystal grain region and a smaller number of crystal grain boundaries than Example 1, and are therefore expected to have a higher residual resistance ratio than Example 1. [Industrial Applicability]
[0067] The aluminum member according to the embodiment of the present invention has a purity of 5N or more and has sufficient strength at least in a part thereof, and is therefore suitable as, for example, an electrical and thermal conductive material for cryogenic temperatures. [Explanation of symbols]
[0068] 1 Fine grain region 2. Intermediate grain region 3 Coarse grain region
Claims
1. A fine grain region having a grain size of less than 20 μm; An intermediate crystal grain region having a crystal grain size of 20 μm or more and less than 150 μm; A coarse crystal grain region having a crystal grain size of 150 μm or more; An aluminum member having an Al content of 99.999 mass % or more.
2. 2. The aluminum member according to claim 1, wherein the fine crystal grain region has an average crystal grain size of 5 μm or less.
3. At least one surface of the fine grain region is less than 0.01 mm 2 The aluminum member according to claim 1 or 2, wherein the first and second insulating layers are present continuously over an area of at least one of the above.
4. A cryogenic electrical and thermal conductive material comprising the aluminum member according to any one of claims 1 to 3.
5. The method for producing the aluminum member according to any one of claims 1 to 3, comprising a friction stirring step of moving a rotating cylindrical jig while pressing it against a surface of an aluminum plate having an Al content of 99.999% by mass or more, wherein the moving speed of the cylindrical jig is 100 mm / min or less.
6. 6. The method according to claim 5, wherein in the friction stirring step, the cylindrical jig is moved with the rotation axis of the cylindrical jig tilted by 3° or more from a perpendicular line to the surface of the aluminum plate in a direction opposite to the moving direction of the cylindrical jig.
Citation Information
Patent Citations
Highly pure aluminum conductor for extremely low temperature and its preparation
JP1995166283A
High purity aluminum rolled sheet and method for producing the rolled sheet
JP2011084800A
JPP4212641B